Ethnobotany of the Himalayas: A book Review - Malik, Zubair A. (Ethnobotany Research and Applications, 2022)
Ethnobotany of the Himalayas. Ripu M. Kunwar, Hassan Sher and Rainer W. Bussmann (Eds). Springer Nature Switzerland AG 2021. xliv + 2185 pp. Price: € 899.99, Print ISBN 978-3-030-57407-9; Online ISBN 978-3-030-57408-6; doi: https://doi.org/10.1007/978-3-030-57408-6